Investigating the impact of leadership on work engagement of employees within the Khomas region, Namibia - Pieters, Wesley; M. N., Hough; M.K., Gaomas; C.V., Tibinyane (Namibian Journal for Research, Science and Technology, 2022)
Leadership has an effect on constructive or deviant behaviour and the work engagement levels of employees. Considering the current economic and social climate of Namibia, it is of utmost importance that leaders initiate and identify ways in which work engagement can be enhanced. Making use of an electronic survey (survey research), this study investigated the effects of different leadership styles on work engagement of employees in the Khomas region. An analysis of the data was done with SPSS (version 24), making use of Pearson’s correlation and Stepwise multiple regression. Work engagement reported a negative relationship with transactional and laissez-faire leadership; a positive relationship was reported with transformational leadership. Transactional (negative) and transformational (positive) leadership were found to be significant predictors of work engagement. Leaders need to avoid compulsive focus on the mistakes or failures of employees. Focusing constantly on mistakes, problems and failures may cause anxiety amongst employees and halt work engagement. Work engagement can be enhanced when leaders clearly and confidently communicate performance standards and expectations; provide praise and recognition; involve employees in decision making whilst discussing different approaches to task completion; and help to develop employees based on their individual strengths and abilities. This study may add to existing knowledge within Industrial/Organizational Psychology, leadership and interventions to improve work engagement and performance of employees.